Percutaneous tracheostomy and cricothyrotomy techniques. Issue 4 (April 2020) - Doody, Nicola; Smart, Neil
Abstract: Percutaneous tracheostomy is an increasingly common procedure performed in the intensive care unit setting. This review discusses the evidence behind its use, provides detailed description of the techniques, and considers the principles of post-tracheostomy care based on recent national audit. It also outlines the most recent recommendations for emergency front of neck access, an essential skill for all anaesthetists and other emergency specialists.